(untitled) (Bangladesh Journal of Medicine, 2019)
Background: Chikungunya is known as a mosquito-borne viral disease. It is transmitted to the human body by infected mosquitoes and caused different symptoms. The main aim of this study was to investigate the percentage of Chikungunya virus disease (CHIKV) patients who would had different clinical features at the acute or sub-acute stage of this disease in Bangladesh. Methodology: In this meta-analysis, PubMed Central and BanglaJOL had been searched. Total 8 eligible studies had been selected for quantitative analysis. The pooled prevalence (PP) was used as effect measure to find the number of patients who would had different symptoms at acute or subacute stage of CHIKV disease. The pooled prevalence and 95% confidence interval (CI) had been calculated using random effects model. To measure the presence of heterogeneity Cochran chi-square test was used and I2 was used to quantify the heterogeneity. Result: This meta-analysis indicated significant association between CHIKV disease patients and fever was [PP: 0.99; p-value = 0.00], joint pain [PP: 0.95, p-value = 0.00], rash [PP: 0.55, p-value = 0.00], joint swelling [PP: 0.38, p-value = 0.001], headache [PP: 0.48, p-value = 0.007], pruritus [PP: 0.37, p-value = 0.001], myalgia [PP: 0.62, p-value = 0.00], co-morbidity [PP: 0.56, p-value = 0.001] at the acute stage of the disease and joint pain persists > 1 month [PP: 0.50, p-value = 0.001] at the subacute stage of this disease. Conclusion: In this meta-analysis ever, joint pain were found as most frequently occurred symptoms at the acute stage of CHIKV disease. Bangladesh J Medicine July 2019; 30(2) : 71-77